How financially literate is today's youth? - Sabri, Mohamad Fazli; Lee, May Poh (Asian Economic and Social Society, 2017)
The current study investigated the level of financial literacy of youth in Malaysia. Quantitative questionnaires were used to test the financial literacy by examining the financial knowledge, practices and attitudes towards money, money management and entrepreneurship of youth in Malaysia. A sample consisting of 220 secondary school students from five schools in Kuala Lumpur, Malaysia had participated in the study. Cross tabulation was used to understand the background of respondents better which included the gender (male and female) and the ethnic group (Malay, Chinese and Indian) of the youth. The findings indicated that male youths are better-informed on financial management and money matters compared to the females. From the survey, Indians have lower level of financial related knowledge compared to other ethnic groups. In addition, both genders had revealed that they have positive attitudes and good practices money matters. These findings contributed to the development of financial empowerment program of youth in Malaysia. The study provides awareness to the public regarding the importance of financial planning in the present and the future as well.